Immune-mediated Gastritis in a Patient with metastatic Lung Cancer due to Therapy with the immune Checkpoint Inhibitor Pembrolizumab – Differences and Similarities in Comparison to “endogenous” autoimmune Type A Gastritis and a review of literature - Ecker, Miriam Eva; Weckauf, Helgard; Tebbe, Sandra; Schuppert, Frank (Zeitschrift für Gastroenterologie, 2023)
Immune checkpoint inhibitors are increasingly used in advanced malignant diseases and are well-known for their good results. With the blockade of immune checkpoints, the probability of immune-related adverse events is also increased.We present a 54-year-old female patient with advanced NSCLC. She was treated with pembrolizumab and developed a stable disease under therapy. After six cycles, she presented with massive epigastric pain to our emergency department. Gastroscopy showed severe erosive-fibrinous pangastritis without the involvement of the esophagus, duodenum, or other immune-related adverse effects. Histology showed the complete destruction of the gastric mucosa. We concluded an immune-mediated gastritis by pembrolizumab, after the exclusion of other differential diagnoses.Despite treatment with prednisolone and marked improvement of her symptoms, the mucosa was never fully reconstituted into a healthy mucosa.Furthermore, we collected published reports of similar cases and conducted a comparison with features of a typical, endogenous type A gastritis to highlight similarities and differences.
Keywords: Immunvermittelte Gastritis; Autoimmungastritis; Typ A Gastritis; Nicht-kleinzelliges Bronchialkarzinom; Immuncheckpoint-Inhibitor; Pembrolizumab